2021
DOI: 10.36547/ams.25.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Localised Corrosion of Stainless Steels 316l and 2205 in Synthetic Bentonite Pore Water and Bentonite Slurry

Abstract: One concept for Czech canister construction for deep geological repository considers stainless steel as an inner case material. Corrosion resistance to localised (pitting/crevice) corrosion and stress corrosion cracking of austenitic stainless steel 316L and duplex steel 2205 was studied. The environment was synthetic bentonite pore water (SBPOW) of domestic bentonite BaM, or a slurry of bentonite in SBPOW. Tests were carried out between 40 °C and 90 °C under anaerobic conditions of a nitrogen atmosphere. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This would result in dry and uniform oxidation on the surface of the canisters. Studies conducted by Stoulil et al [153] have shown that high temperatures compact the corrosion layers on the surface of the canisters, which slightly reduces the corrosion rate. Schlegel et al [154] showed that under fluctuating temperature conditions (85 • C with a drop to 25 • C, and then 85 • C again), steel corrosion presented areas of extensive corrosion with depressions filled with corrosive products.…”
Section: Effect Of Oxygen Gasses and Nutrients On The Microorganismsmentioning
confidence: 99%
“…This would result in dry and uniform oxidation on the surface of the canisters. Studies conducted by Stoulil et al [153] have shown that high temperatures compact the corrosion layers on the surface of the canisters, which slightly reduces the corrosion rate. Schlegel et al [154] showed that under fluctuating temperature conditions (85 • C with a drop to 25 • C, and then 85 • C again), steel corrosion presented areas of extensive corrosion with depressions filled with corrosive products.…”
Section: Effect Of Oxygen Gasses and Nutrients On The Microorganismsmentioning
confidence: 99%